Patient-Planetary Health Co-benefit Prescribing: Emerging Considerations for Health Policy and Health Professional Practice - Redvers, Nicole (Frontiers in Public Health, 2021)
In addition to the importance of fostering and developing measures for better health-system resilience globally from the effects of climate change, there have been increasing calls for health professionals, as well as public health and medical education systems, to become partners in climate change mitigation efforts. Direct clinical practice considerations, however, have not been adequately fostered equitably across all regions with an often-confusing array of practice areas within planetary health and sustainable healthcare. This article calls for a more coordinated effort within clinical practice spaces given the urgency of global environmental change, while also taking lessons from Indigenous traditional knowledge systems—a viewpoint that is rarely heard from or prioritized in public health or medicine. Simpler and more coordinated messaging in efforts to improve patient and planetary health are needed. The creation of unifying terminology within planetary health-rooted clinical and public health practice has been proposed with the potential to bring forth dialogue between and within disciplinary offshoots and public health advocacy efforts, and within clinical and health-system policy spaces.